Method for reinforcing phosphorus building gypsum by using waste fibers and thermoplastic plastics
By making waste fibers and thermoplastics into fibrous particles and modifying and strengthening them with phosphorus building gypsum powder, the problem of insufficient strength of traditional phosphorus building gypsum powder is solved, high-strength building gypsum materials are achieved, and the recycling of waste is promoted.
Patent Information
- Application Number
- CN202411560011.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-03-14
AI Technical Summary
Traditional phosphorus building gypsum powder is insufficient in terms of strength, especially when it is damp, high temperature or affected by external forces, its performance is difficult to meet the use requirements, resulting in bottlenecks in the promotion and application of building materials products.
By crushing the discarded fibers and thermoplastics into fibrous particles and evenly adding them to phosphorus building gypsum powder for modification and strengthening, graphene is used to modify and modify the fibrous particles to increase the specific surface area and compatibility, and improve adhesion.
The flexural strength and compressive strength of phosphorus building gypsum have been significantly improved, reaching the standard of building gypsum 3.0, and at the same time alleviating the ecological environment pollution caused by plastic waste, achieving the purpose of waste control and waste recycling.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid waste material recycling, and in particular to a method for reinforcing phosphorus building gypsum by utilizing waste fibers and thermoplastic plastics. Background Art
[0002] Phosphogypsum is a solid byproduct produced during the wet production of phosphoric acid, that is, after the reaction of phosphate rock and sulfuric acid, phosphoric acid and phosphogypsum are generated. For every ton of phosphoric acid produced, 4.8 to 5.0 tons of phosphogypsum will be produced. At present, China's average annual phosphogypsum emissions exceed 70 million tons, and the global phosphogypsum emissions are 185 million to 215 million tons per year. A large amount of phosphogypsum is piled up and occupies land, seriously polluting the surrounding soil and water resources. In addition, there is a lack of efficient phosphogypsum recycling technology. It is urgent to strengthen the resource utilization, efficiency and harmlessness of phosphogypsum.
[0003] The main component of phosphogypsum is calcium sulfate dihydrate, and its content is usually above 85%. After high-temperature calcination, phosphogypsum becomes phosphogypsum, which can react with water and solidify and harden, and can be used as a cementitious material in construction and other fields. However, since phosphogypsum contains a small amount of undecomposed calcium fluorophosphate, residual acid, fluoride, acid insoluble matter, organic matter, heavy metals and other impurities, the presence of these impurities greatly limits the resource utilization of phosphogypsum and has an important impact on the quality of downstream phosphogypsum products.
[0004] As an important building material, phosphorus building gypsum powder has been widely used in the construction industry due to its good processing performance, excellent gelling properties and relatively low cost. However, with the continuous development of the construction industry and the improvement of people's requirements for the performance of building materials, the shortcomings of traditional phosphorus building gypsum powder in strength have gradually emerged. Especially in some special environments, such as humidity, high temperature or external impact, its performance is often difficult to meet the use requirements, resulting in bottlenecks in the promotion and application of building materials products. Therefore, how to economically and effectively enhance phosphorus building gypsum has become a current research hotspot.
[0005] The Chinese patent application with application number 202010672955.7 discloses a method for preparing building gypsum based on modified phosphogypsum, comprising the following steps: by weight, 0.01-0.5 parts of hydroxypropyl methylcellulose, 0.5-2 parts of redispersible latex powder, 2-4 parts of expanded perlite, and 0.02-0.08 parts of calcium salt of amino acid oligomers are mixed, and then 50-58 parts of modified phosphogypsum, 5-7 parts of heavy calcium powder, 1-2 parts of vitrified microbeads, and 20-25 parts of quartz sand are added to mix to obtain building gypsum; the preparation method of modified phosphogypsum is specifically as follows: S1, crushing the phosphogypsum and sieving to obtain sieved phosphogypsum; S2, pretreating the sieved phosphogypsum using an autoclave to obtain a pretreated material; S3, frying the pretreated material to obtain modified phosphogypsum. This method uses a variety of chemical additives and special materials, which improves the performance of building plaster to a certain extent, but the price of raw materials and production costs are relatively high, and the discarded building plaster may cause a certain burden on the environment because it contains a variety of chemical components.
[0006] The Chinese patent application with application number 202310565508.5 discloses a fiber-reinforced gypsum composite material, including the following components by mass: 100 parts of phosphogypsum, 45-60 parts of water, 0.5-3.5 parts of calcium oxide, 0.2-0.6 parts of polypropylene fiber, 0.1-0.3 parts of polyvinyl alcohol fiber, 0.1-0.6 parts of polyphosphate, 0.2-0.6 parts of silane coupling agent, 0.1-0.3 parts of latex and 0.1-0.5 parts of water reducer. This method uses a variety of fibers. Since the fibers themselves are slender, it is difficult to mix them evenly. Therefore, it is difficult to optimize the force transmission path through synergy, thereby improving the performance of the matrix. In addition, the use of multiple fibers and admixtures greatly increases the cost of the product.
[0007] Fibrous materials are prepared by recycling plastic waste such as discarded masks, discarded plastic bottles, and discarded packaging bags, and then evenly added to phosphorus building gypsum powder for modification and enhancement. On the one hand, the mechanical properties of phosphorus building gypsum powder are improved, and on the other hand, the ecological environmental pollution caused by plastic waste is alleviated, achieving the purpose of waste treatment and waste recycling. Summary of the invention
[0008] In view of the above problems, the present invention provides a method for reinforcing phosphorus building gypsum by using waste fibers and thermoplastic plastics, which can not only enhance and modify the phosphorus building gypsum, but also improve the recycling rate of waste, alleviate the ecological environment pollution caused by plastic waste, and achieve the purpose of treating waste with waste and utilizing waste.
[0009] The method for reinforcing phosphorus building plaster by using waste fibers and thermoplastics comprises the following steps: crushing the waste fibers and thermoplastics to obtain fibrous particles, and adding the fibrous particles into phosphorus building plaster powder for uniform mixing.
[0010] As a preferred solution, the fibers include discarded masks with metal nose clips and cotton ear loops removed.
[0011] As a preferred solution, the thermoplastic plastic includes at least one of a plastic bottle, a packaging bag or a plastic wrap.
[0012] As a preferred solution, the fibers and thermoplastics are cleaned and sterilized with alcohol before being crushed, and redundant parts are removed, and then cut into pieces with a length of 8 to 12 cm and a width of 4 to 6 cm.
[0013] As a preferred solution, the specific process of the pulverization is: adding a proper amount of water to the fiber and the thermoplastic plastic to prepare a slurry, and then putting it into a high-speed crusher for shearing and crushing.
[0014] As a more preferred solution, the shear rate of the high-speed crusher is 2000~3000 r / min, and the shear time is 5~10 min.
[0015] As a preferred solution, the fibrous particles have a length of 5 to 30 mm and a diameter of 5 to 30 um.
[0016] As a preferred solution, the fibrous particles obtained after crushing are dried in an oven at 40-60°C.
[0017] As a preferred solution, the surface of the fibrous particles is modified by using graphene. The fibrous particles treated with a surface modifier, graphene oxide solution, are uniformly mixed into the phosphorus building gypsum powder for modification and reinforcement. Since a layer of coating is formed on the surface of the fibrous particles after being treated with the graphene oxide solution, the specific surface area is increased, the compatibility and adhesion of organic and inorganic substances are improved, and it is more conducive to enhancing the mechanical properties of the phosphorus building gypsum. As a more preferred solution, the method of modifying the surface of the fibrous particles by using graphene is as follows: adding the fibrous particles to a 0.02% to 0.1% by mass graphene oxide aqueous solution and stirring for 1 to 6 hours, then filtering and drying in an oven at 40 to 60°C to complete the modification. As a preferred solution, the solid-to-liquid ratio of the fibrous particles to the graphene oxide solution is 1:10 to 20.
[0018] As a preferred solution, the amount of the fibrous particles added to the phosphorus building gypsum powder is 0.5% to 2% of the mass of the phosphorus building gypsum powder.
[0019] As a preferred solution, in order to allow the fibrous particles to be evenly incorporated into the phosphorus building gypsum powder, the fibrous particles and the phosphorus building gypsum powder are mixed at a rotation speed of 65 to 100 r / min for 15 to 60 min.
[0020] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention regenerates waste fibers and thermoplastics into fibrous particles, which are then uniformly added to phosphorus building gypsum powder for modification and enhancement. In addition, in order to further improve the strength of phosphorus building gypsum, the present invention also uses graphene to modify the surface of the fibrous particles. After the fibrous particles are treated with a graphene oxide solution, a coating is formed on the surface of the fibrous particles, which increases the specific surface area, improves the compatibility and adhesion of organic and inorganic substances, and is more conducive to enhancing the mechanical properties of phosphorus building gypsum powder. The present invention alleviates the ecological environment pollution caused by plastic waste and achieves the purpose of treating waste with waste and utilizing waste.
[0021] 2. The present invention uses waste fibers and thermoplastics as reinforcing materials, thereby achieving effective recycling and reuse of waste, reducing environmental pollution, and conforming to the concept of sustainable development. At the same time, the use of low-cost or zero-cost waste materials to replace traditional reinforcing materials can significantly reduce the production and use costs of phosphorus building gypsum.
[0022] 3. The method provided by the present invention is used to modify and strengthen phosphorus building gypsum. After testing, the flexural strength and compressive strength of the test piece are improved by at least 20% and 10% respectively compared with the unmodified ones, reaching the quality standard of building gypsum strength grade 3.0.
[0023] 4. The method of the present invention is simple and easy to implement, does not require complicated equipment and technology, and is easy to promote and apply in actual production. The present invention not only helps to solve the problem of waste disposal, but also improves the performance of building materials and reduces costs. It is an environmentally friendly and economical and practical technological innovation. DETAILED DESCRIPTION
[0024] The technical scheme of the present invention is further described below by way of examples. The raw materials used in the examples can be purchased from the market or prepared by conventional methods.
[0025] The 2 h flexural strength of the phosphorus building gypsum used in the embodiment of the present invention is 2.8 MPa, and the 2 h compressive strength is 5.7 MPa.
[0026] Example 1 A method for reinforcing phosphorus building plaster using waste fibers and thermoplastics comprises the following steps: The metal nose bridge and cotton earrings of the recycled discarded masks were cut off and cleaned and disinfected with alcohol. Then they were cut into pieces of 8-12 cm in length and 4-6 cm in width and an appropriate amount of water was added to prepare a slurry. The slurry was then placed in a high-speed crusher for shearing and crushing at a shear rate of 2500 r / min and a shearing time of 10 min. After the shearing and crushing was completed, the fibrous particles were placed in a 50 ℃ oven and dried to constant weight.
[0027] After microscopic observation and measurement, the prepared fibrous particles are about 10 mm in length and 10 um in diameter.
[0028] Then, the fibrous particles were added into a 0.05% by mass graphene oxide aqueous solution at a solid-liquid ratio of 1:10 for surface modification for 2 h. After the modification, they were filtered and placed in a 50 °C oven to dry.
[0029] Finally, the prepared 1% fibrous particles were fully mixed with the phosphorus building gypsum powder at a mixing speed of 100 r / min and a mixing time of 60 min.
[0030] According to GB / T17669.3-1999 Determination of Mechanical Properties of Building Gypsum, the strength of the modified phosphorus building gypsum was tested. The 2-hour flexural strength was 3.8 MPa and the 2-hour compressive strength was 6.6 MPa. It can be seen that the phosphorus building gypsum powder modified by the prepared fibrous particles has good mechanical properties and has reached the standard of building gypsum 3.0.
[0031] Example 2 A method for reinforcing phosphorus building plaster using waste fibers and thermoplastics comprises the following steps: The metal nose bridge and cotton earrings of the recycled discarded masks were cut off and cleaned and disinfected with alcohol. Then they were cut into pieces of 8-12 cm in length and 4-6 cm in width and an appropriate amount of water was added to prepare a slurry. The slurry was then placed in a high-speed crusher for shearing and crushing at a shear rate of 2500 r / min and a shearing time of 10 min. After the shearing and crushing was completed, the fibrous particles were placed in a 50 ℃ oven and dried to constant weight.
[0032] After microscopic observation and measurement, the prepared fibrous particles are about 10 mm in length and 10 um in diameter.
[0033] Then the prepared 1% fibrous particles were fully mixed with the phosphorus building gypsum powder at a mixing speed of 100 r / min and a mixing time of 60 min.
[0034] The strength of the modified phosphorus building gypsum was tested according to GB / T17669.3-1999 Determination of Mechanical Properties of Building Gypsum. The 2 h flexural strength was 3.5 MPa and the 2 h compressive strength was 6.4 MPa. Compared with Example 1, the fibrous particles that were not surface-modified by the graphene oxide solution had poor compatibility with the gypsum powder, resulting in a certain degree of reduction in its strength.
[0035] Example 3 A method for reinforcing phosphorus building plaster using waste fibers and thermoplastics comprises the following steps: The recycled waste plastic bottles were cleaned and disinfected with alcohol, then cut into pieces of 8-12 cm in length and 4-6 cm in width and added with an appropriate amount of water to prepare a slurry, which was then placed in a high-speed crusher for shearing and crushing at a shear rate of 2000 r / min and a shearing time of 10 min. After the shearing and crushing was completed, the fibrous particles were placed in a 50 °C oven and dried to constant weight.
[0036] After microscopic observation and measurement, the prepared fibrous particles are about 24 mm in length and about 18 um in diameter.
[0037] Then, the fibrous particles were added into a 0.1% by mass graphene oxide aqueous solution at a solid-liquid ratio of 1:10 for surface modification for 5 h. After the modification, they were filtered and placed in a 50 °C oven to dry.
[0038] Finally, the prepared 1.5% fibrous particles were fully mixed with the phosphorus building gypsum powder at a mixing speed of 100 r / min and a mixing time of 60 min.
[0039] According to GB / T17669.3-1999 Determination of Mechanical Properties of Building Gypsum, the strength of the modified phosphorus building gypsum was tested. The 2-hour flexural strength was 3.6 MPa and the 2-hour compressive strength was 6.3 MPa. It can be seen that the phosphorus building gypsum powder modified with fibrous particles has good mechanical properties and has reached the standard of building gypsum 3.0.
[0040] Example 4 A method for reinforcing phosphorus building plaster using waste fibers and thermoplastics comprises the following steps: The recycled waste packaging plastic bags were cleaned and disinfected with alcohol, then cut into pieces of 8-12 cm in length and 4-6 cm in width and added with an appropriate amount of water to prepare a slurry, which was then placed in a high-speed crusher for shearing and crushing at a shear rate of 3000 r / min and a shearing time of 10 min. After the shearing and crushing was completed, the fibrous particles were placed in a 50 °C oven and dried to constant weight.
[0041] After microscopic observation and measurement, the prepared fibrous particles are about 6 mm in length and about 7 um in diameter.
[0042] Then, the fibrous particles were added into a 0.1% by mass graphene oxide aqueous solution at a solid-liquid ratio of 1:10 for surface modification for 5 h. After the modification, they were filtered and placed in a 50 °C oven to dry.
[0043] Finally, the prepared 0.5% fibrous particles were fully mixed with the phosphorus building gypsum powder at a mixing speed of 100 r / min and a mixing time of 60 min.
[0044] According to GB / T17669.3-1999 Determination of Mechanical Properties of Building Gypsum, the strength of the modified phosphorus building gypsum was tested. The 2-hour flexural strength was 3.4 MPa and the 2-hour compressive strength was 6.4 MPa. It can be seen that the phosphorus building gypsum powder modified with fibrous particles has good mechanical properties and has reached the standard of building gypsum 3.0.
[0045] It should be understood that the above embodiments are only used to illustrate the present invention and are not used to limit the scope of protection of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the appended claims of the present application.
Claims
1. A method for reinforcing phosphorus building plaster using waste fibers and thermoplastics, characterized in that: The method comprises the following steps: crushing waste fibers and thermoplastic plastics to obtain fibrous particles, and adding the fibrous particles into phosphorus building gypsum powder for uniform mixing.
2. The method for reinforcing phosphorus building plaster using waste fibers and thermoplastics according to claim 1, characterized in that: The fibers include discarded masks without metal nose clips and cotton earrings; and the thermoplastic plastic includes at least one of a plastic bottle, a packaging bag or a plastic wrap.
3. The method for reinforcing phosphorus building plaster using waste fibers and thermoplastics according to claim 1, characterized in that: Before being crushed, the fibers and thermoplastics are cleaned and sterilized with alcohol, redundant parts are removed, and then cut into pieces with a length of 8 to 12 cm and a width of 4 to 6 cm.
4. The method for reinforcing phosphorus building plaster using waste fibers and thermoplastics according to claim 1, characterized in that: The specific process of the pulverization is: adding an appropriate amount of water to the fiber and the thermoplastic plastic to prepare a slurry, and then putting it into a high-speed crusher for shearing and crushing.
5. The method for reinforcing phosphorus building plaster using waste fibers and thermoplastics according to claim 4, characterized in that: The shear rate of the high-speed crusher is 2000-3000 r / min, and the shear time is 5-10 min.
6. The method for reinforcing phosphorus building plaster using waste fibers and thermoplastics according to claim 1, characterized in that: The length of the fibrous particles is 5-30 mm and the diameter is 5-30 um.
7. The method for reinforcing phosphorus building plaster using waste fibers and thermoplastics according to claim 1, characterized in that: The crushed fibrous particles are dried in an oven at 40-60 °C.
8. The method for reinforcing phosphorus building plaster using waste fibers and thermoplastics according to claim 1, characterized in that: Graphene is used to modify the surface of the fibrous particles.
9. The method for reinforcing phosphorus building plaster using waste fibers and thermoplastics according to claim 8, characterized in that: The method for modifying the surface of the fibrous particles by using graphene is as follows: adding the fibrous particles to a 0.02% to 0.1% mass fraction of graphene oxide aqueous solution and stirring for 1 to 6 hours, then filtering and drying in an oven at 40 to 60°C to complete the modification.
10. The method for reinforcing phosphorus building plaster using waste fibers and thermoplastics according to claim 1, characterized in that: The amount of the fibrous particles added to the phosphorus building gypsum powder is 0.5% to 2% of the mass of the phosphorus building gypsum powder; the fibrous particles and the phosphorus building gypsum powder are mixed at a rotation speed of 65 to 100 r / min for 15 to 60 minutes.
Citation Information
Patent Citations
Preparation method of building gypsum based on modified phosphogypsum
CN111763058A
Fiber reinforced gypsum composite material and gypsum mold box
CN116606116A